Usulan Pengelolaan Potensi Desa Giriasih Wisata Embung Bem-Bem Dan Pembangunan Omah Singkong - Nernere, Maria Setyaningsih (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2021)
Giriasih Village is a village located in Purwosari sub- district, Gunungkidul Regency, DI Yogyakarta. Giriasih Village has a lot of village potential, but among the many potential villages it has, Embung Bem-bem tourism object. It is the object has natural beauty and high prospects for progress with good management. Giriasih Village, which is rich in natural potential, is still unable to manage the natural wealth of the village's potential so that proposals will be made in management. Apart from being rich in tourism village potential, Giriasih village is also a village where the majority of the villagers work as cassava farmers. However, with the existing limitations, people are only able to sell cassava as raw material. This is what human empowerment should then be done to improve the economy from the growth in the selling value of cassava which is not only sold as raw goods but also as finished goods.